They don’t even listen to us: Violent protest as a means to regulate intergroup relations - Waldzus, S.; Dumont, K.; Fiske, A. (42nd Annual Scientific Meeting of The International Society of Political Psychology (ISPP), July 12-15, Lisbon, Portugal, 2019)
Violent and disruptive protest actions are often considered by outside observers or targets of the protest as destructive and non-normative as they violate a widely shared moral norm of not intentionally harming others. At the same time, they are often risky or even harmful for the protesters and their groups and not necessarily effective in relation to the protest’s actual goal. The question is why protesters engage in such violent and disruptive protests anyway. Informed by social identity theory, relational models theory and the concepts of minimal and maximal standards we present a theoretical explanation of violent protest that assumes that violent protest serves the purpose of regulating intergroup relations. We also present first research on the role of relational discrepancy (i.e., between how the relation to the target of the protest should be and how it actually is) in the support for destructive protest actions conducted in the context of social protests in South Africa. Results of a semi structured interview study and of an online correlational study (N = 445) showed that a) some forms of disruptive and violent protest were considered as normative by some participants and non-normative by others, b) relational discrepancy was produced in interviews as justification of violent protest, but c) correlated negatively with support of destructive protest actions when measured in the absence of a specific triggering transgression. Implications for the relational explanation of violent protest will be discussed.